Resonant RF electromagnetic field input in the helicon plasma ion source - Alexenko, O.V.; Miroshnichenko, V.I.; Mordik, S.N. (Вопросы атомной науки и техники, 2014)
Spatial distribution of RF electromagnetic field absorption by a plasma electron subsystem of ion source is studied. An ion source operates in a helicon mode (wci < w < wce < wpe). A simplified model of plasma RF source is used for investigations. Calculations were performed for two particular geometrical dimensions of a discharge chamber with the assumption of two symmetrical modes excitation at two different pressure values of plasma forming gas (helium, hydrogen). The ion source injector parameters of IAP NASU nuclear scanning microprobe were taken for calculations. The calculations show a resonant behaviour of integral RF power absorption as a function of the external magnetic field at a fixed plasma density. Sharpness of resonances becomes smaller as plasma forming gas pressure grows. There is a distribution topography of absorbed power in a discharge chamber for the cases under research. The possible extracted ion current density is evaluated under Bohm criterion.